Effects of Khat (Catha Edulis) on Bronchial Asthma - Eden Yitna; Andualem Mossie; Alemeshet Yami (Open Journal of Asthma - Peertechz Publications, 2018)
Introduction: Asthma is a chronic inflammatory disorder of the airways. It is always being a health burden across the globe. The active chemical present in Khat could have a bronchodilator effect like that of catecholamine. The present study aims at determining the effect of khat chewing on bronchial asthma and lung function. Methods: A comparative cross-sectional study was conducted in Jimma University Specialized Hospital (JUSH) Adult Chest Clinic on 170 asthmatic patients with a 1.4 to 1 ratio of non-chewer to chewer. The interviewer-administered questionnaire, patient history and pulmonary function test using Spirometer were used to collect data.